Putting intellectual property in its place : rights discourses, creative labor, and the everyday - Murray, Laura J., 1965-; Piper, S. Tina; Robertson, Kirsty, 1976- (New York : Oxford University Press, 2014)
This title examines the relationship between creativity and intellectual property law on the premise that, despite concentrated critical attention devoted to IP law from academic policy and activist quarters, its role as a determinant of creative activity is overstated.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Intellectual property; Copyright; Intellectual property -- United States -- History; Law; Laws of specific jurisdictions & specific areas of law